2011
DOI: 10.1007/s00240-011-0398-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adherence of multi-drug resistant E. coli by proanthocyanidin

Abstract: Proanthocyanidin is commonly used for inhibiting urinary tract infection (UTI) of sensitive strains of Escherichia coli. The aim of this study was to investigate the effect of proanthocyanidin on adherence of uropathogenic multi-drug resistant E. coli to uroepithelial cells, which has not yet been investigated so far. Extracts of the purified proanthocyanidin were prepared from dried cranberry juice. Purity and structural assignment of proanthocyanidin was assessed using high performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…Since E. coli can adhere better in diabetic females than in healthy subjects [43], the abundance of E. coli in T2DM patients’ urine should be higher than controls. However, no difference was found in the abundance of E. coli between the two cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Since E. coli can adhere better in diabetic females than in healthy subjects [43], the abundance of E. coli in T2DM patients’ urine should be higher than controls. However, no difference was found in the abundance of E. coli between the two cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the activity of EGCG against E. coli, it has been found that EGCG interacts with the porin protein of the outer membrane of E. coli, thereby inhibiting the major function of the porin, namely the transport of small hydrophilic molecules such as glucose, finally leading to inhibition against the growth of E. coli [116]. Besides, it has been revealed that the proanthocyanidin offers protection against both sensitive as well as multi-drug resistant strains of E. coli by inhibiting the adherence of multi-drug resistant strains on uroepithelial cells [67]. Similar mechanism has also been proposed for tea components inhibiting the attachment and subsequent biofilm formation of S. mutans on tooth surfaces.…”
Section: Mechanismmentioning
confidence: 98%
“…They have been reported to be effective antibacterial agents against both sensitive and multi-drug resistant strains [67,68]. Proanthoxyanidins are divided into two types according to the linkage between the flavans: type A refers to those where constituent flavanyl moieties are linked via only one bond, while type B posses an second ether linkage to C (2) of the terminal flavanyl unit (Fig.…”
Section: Flavanolsmentioning
confidence: 99%
“…In this scenario, treatment failure can negatively affect the quality of life of patients with recurrent UTIs and can also cause a non-negligible cost for the healthcare system. Nonpharmacological oral supplements, including cranberry proanthocyanidins [14][15][16] and probiotics [17], have been evaluated for the prevention of UTIs. Although it is recognized that more research is needed, the use of nonpharmacological products to prevent UTIs should be considered a useful and safe alternative to antibiotics in this era of increasing antibiotic resistance [17].…”
mentioning
confidence: 99%